Strategi penterjemahan mainan kata dari Bahasa Inggeris ke Bahasa Cina dalam Alice's Adventures in Wonderland / Chen Seok Yuen - Chen, Seok Yuen (2012)
Wordplay is a literary form which exploit ats least two meaning of a word or a phrase. When source text writer uses wordplay to generate humor effect or specific understanding, the choice of translation strategy is a major challenge because the translation must not only be accurate, but also raise target reader sensitivity to understand the message. This study aims to provide a non-evaluative description in order to come to a better understanding of the problem and solutions in wordplay translation from English to Chinese. The earliest Chinese translation Alice’s Adventures in Wonderland (阿丽丝漫游奇境记) translated by a structuralist linguist, Chao Yuen Ren in 1922. In this study, wordplay in the source text is analyzed and categorized following two criteria namely formal structure and linguistic features. Half of the wordplay in source text created by Lewis Carroll is based on phonological features. The findings show that the translator uses three different translation strategies based on translation analyse of Dirk Delabastita (1993). Overall, Chao’s translation did not only provide surface meaning but made an effort to maintain wordplays in his translation in order to retain the source text writer's language style. In this way the characteristics of the source text is preserved and appreciated by the target text readers.